Histology of Maca, Lepidium meyenii Walpers (Brassicaceae) - Marín-Bravo, Manuel (2003)
The histological study of Lepidium meyenii Walpers "maca" is focused mainly on the characterization of the underground storage organ. The study was carried out with yellow macas from Junín, and it comprises the histological study of the storage organ and additionally details of internal structure of the leaves from samples fixed in FAA and using the inclusion in paraffin technique. The results show in the storage organ the characteristics of a transitional region among the root of a lignified structure and a reduced primary stem, with the development of a wide medullar area. Additionally, there is a characteristic secondary cambial activity in the cortical area. Likewise, among the additional histological details reported for this plant, is the development of a suberized lining of cortical cells in the storage organ and conical unicellular trichomes in the surface of the leaves.